2019
DOI: 10.1186/s12891-019-2899-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic capability of dynamic ultrasound evaluation of supination-external rotation ankle injuries: a cadaveric study

Abstract: BackgroundAnkle syndesmosis injuries are common and range in severity from subclinical to grossly unstable. Definitive diagnosis of these injuries can be made with plain film radiographs, but are often missed when severity or image quality is low. Computed tomography (CT) and magnetic resonance imaging (MRI) can provide definitive diagnosis, but are costly and introduce the patient to radiation when CT is used. Ultrasonography may circumvent many of these disadvantages by being inexpensive, efficient, and able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…This modality allows evaluation of dynamic movements of the fibula, and physiological fibular movements can be evaluated by US even in the normal ankle [ 11 ]. As for the evaluation of syndesmosis instability, a method of measuring tibiofibular distance by US has been reported (as applied in this study) [ 13 ]. In that cadaveric experiment, distance between the tibia and fibula was quantitatively evaluated by adding external rotation stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This modality allows evaluation of dynamic movements of the fibula, and physiological fibular movements can be evaluated by US even in the normal ankle [ 11 ]. As for the evaluation of syndesmosis instability, a method of measuring tibiofibular distance by US has been reported (as applied in this study) [ 13 ]. In that cadaveric experiment, distance between the tibia and fibula was quantitatively evaluated by adding external rotation stress.…”
Section: Discussionmentioning
confidence: 99%
“…Since quantitative evaluations can be performed with US, syndesmotic instability could be evaluated by measuring the distance between the tibia and fibula. Evaluation under loading with external rotation stress has been reported, but results under other stresses remain unknown [ 13 ]. In addition, applying stress loads to acute syndesmosis injuries remains unsafe because of the invasiveness to patients.…”
Section: Introductionmentioning
confidence: 99%
“…11 More recently, Fisher et al have reported that dynamic external rotation stress evaluation using ultrasonography was able to detect a significant difference between the uninjured ankle with a tibiofibular clear space of 4.5 mm and the stage 1 complete injured ankle with a clear space of 6.0 mm. 33 In the future, the increase in access to Weight-Bearing Computed Tomography may improve our diagnostic capability of ankle instability. Patel et al, have already published their work defining the reference values of the normal tibiofibular syndesmosis using the weight bearing CT, which will be useful when this modality becomes more widely available.…”
Section: Preoperative Assessmentmentioning
confidence: 99%
“…As a consequence, no consensus has yet been reached on the definition of clinically consequential syndesmotic instability. Ultrasonography is increasingly used in the diagnosis of syndesmotic instability as it allows for a bilateral dynamic evaluation of the ankle joint at the point of care with little risk to the patient and at low cost [ 1 , 13 , 18 , 32 ].…”
Section: Discussionmentioning
confidence: 99%